1989
DOI: 10.1002/bdd.2510100502
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic models for monooxygenases

Abstract: The microsomal mixed function oxidase system contains the cytochrome P-450 oxidative drug metabolizing family of enzymes, The catalytic cycle of cytochrome P-450 is believed to involve the formation of an active iron-oxygen species which is responsible for oxygen transfer to the substrate. This assumption is supported by the fact that a number of peroxidative agents can replace NADPH, the reductase, and oxygen as co-reactants in most oxidative reactions of microsomal cytochrome P-450. We have found that a mixt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Under direct excitation of DBCH, radicals may be produced from its triplet state under oxidative conditions. 24,25 According to our data, oxygen quenches the PTL-HCl triplet state with a bimolecular rate constant in the range of (4.37-7.54) × 10 8 M -1 s -1 . Obviously, this explains why there is no dimer formation.…”
Section: Resultsmentioning
confidence: 94%
“…Under direct excitation of DBCH, radicals may be produced from its triplet state under oxidative conditions. 24,25 According to our data, oxygen quenches the PTL-HCl triplet state with a bimolecular rate constant in the range of (4.37-7.54) × 10 8 M -1 s -1 . Obviously, this explains why there is no dimer formation.…”
Section: Resultsmentioning
confidence: 94%
“…Complexation of this electron-rich pyridone oxygen atom to a high-valent, electrondeficient iron-oxo species within hepatic cytochrome P-450 would facilitate hydrogen loss from C (6). Hydrogen atom abstraction would occur through a six membered, cyclic transition state [25,26]. Finally, the loss of a C(6) hydrogen would create a resonance-stabilized radical conjugated through the central double bond (D 5a,9a ) to the lonepair electrons of the pyridone nitrogen atom.…”
Section: Discussionmentioning
confidence: 99%
“…159 The oxidative pathway of stilbene and its tricyclic derivatives with both Fenton (Fe(II)/H 2 O 2 ) and Ruff (Fe(III)/H 2 O 2 ) reagents was reported as a biomimetic simulation for the oxidative metabolism of cytochrome P-450 activation, which plays a significant role in chemical carcinogenesis. 160 The reaction of 5-dibenzosuberenone (1) with Fenton reagent resulted in the formation of trans-10,11-dihydroxy-10,11-dihydro-5H-dibenzo[a,d]cyclohepten-5-one (249), α-hydroxy ketone 250, triketone 40, and aldehyde derivative 251 in addition to the major product epoxide 50 in 52% yield (Scheme 39). The results obtained suggested that the risk of mutagenicity of 1 will probably be reduced due to the relatively high stability of the oxirane ring in 50.…”
Section: Syn Thesismentioning
confidence: 99%